SAT0013 Molecular and Cellular Repsonses to Inhibition of JAK-STAT Signalling in RA Synovial Fibroblasts and Whole Tissue Explants. (9th June 2015) - Orr, C.; Linehan, E.; Gao, W.; Creevey, K.; McGarry, T.; Fearon, U.; Veale, D.J.
Abstract : Background: Rheumatoid Arthritis (RA) is a common, chronic immune-mediated inflammatory disease, characterised by synovitis and progressive destruction of articular cartilage and bone. Janus Kinase and Signal Transducer and Activator of Transcription (JAK/STAT), a critical signalling pathway involved in inflammatory mechanisms, has been implicated in the pathogenesis of RA. Objectives: In this study we examine the effect of Tofacitinib (JAK inhibitor CP-690, 550) on pro-inflammatory pathways in RA using in vitro and ex-vivo culture models. Methods: Primary RA synovial fibroblasts (RASFC) and whole tissue ex vivo RA synovial explant cultures were established from RA biopsies obtained at arthroscopy. Phospho-STAT3 (p-STAT3), phospho-STAT1 (p-STAT1), Suppressor of Cytokine Signaling 3 (SOCS3) and Protein Inhibitor of Activated Stat 3 (PIAS3) expression were quantified by Western Blot in RASFC following culture in the presence of IL-17, OSM and IL-6. RASFC were cultured with IL-17, OSM and IL-6 in the presence or absence of Tofacitinib (1uM) and cytokine secretion in supernatants were measured by ELISA. Ex-vivo RA synovial explants were cultured with Tofacitinib (1uM) and spontaneous secretion of IL-6, IL-8, MMP3, Tie2, PIGF and bFGF were quantified in supernatants by ELISA or MSD multiplex. Finally conditioned media from control and Tofacitinib treated RA explants were cultured with RASFC and cell invasion assessed by Transwell Matrigel™ invasion chambers. Results: IL-17, OSM and IL-6 induced p-STAT3, p-STAT1 expression and inhibited SOCS3 and PIAS3 expression in RASFC. Tofacitinib decreased IL-17, OSM and IL-6 induced cytokine production from RASFC. Tofacitinib inhibited spontaneous release of IL-6, IL-8, MMP3 and soluble Tie2 receptor from RA synovial explant cultures, with no effect observed for PIGF and bFGF. Finally, conditioned media from Tofacitinib treated RA explants inhibited RASFC invasion. Conclusions: This study demonstrates inverse expression of pSTATs and their negative regulators SOCS3/PIAS3 in response to pro-inflammatory mediators in RA. In addition Tofacitinib inhibits pro-inflammatory mediators and RASFC invasion, further confirming a role for JAK-STAT inhibition in the treatment of RA. Disclosure of Interest: None declared